2018
DOI: 10.18551/rjoas.2018-07.34
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compound and Nutritious Characteristic of Bitter Melon Fruit (Momordica Charantia L.)

Abstract: The bitter melon nutritious profile which was full of nutrition all contributed to flexibility towards curing some kind of diseases. The purpose of the research is to investigate nutritious composition of bitter melon (Momordica charantia L.). The parameter used to detect was as follow: ash content, water content, crude protein, crude fat, total carbohydrate, pectin, dietary fiber, calcium, vitamin C, β-carotene, diosgenin, stigmasterol, campesterol and β-sitosterol. The reseach finding showed that the carbohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, the underlying mechanisms of the growth inhibitory effects of M charantia extract and K-J in breast cancer cell remains poorly understood. In some cases, more than one processes occur, however, it is known that apoptosis is the dominant type involving the formation of multiprotein complexes that provide the molecular scaffolding for the activation of the initiator caspases including caspase − 8 (extrinsic pathway), caspase − 9 (intrinsic pathway) and caspase − 3 (executioner caspase caspase-3 pathway [25,26,40,41]. The results presented in Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the underlying mechanisms of the growth inhibitory effects of M charantia extract and K-J in breast cancer cell remains poorly understood. In some cases, more than one processes occur, however, it is known that apoptosis is the dominant type involving the formation of multiprotein complexes that provide the molecular scaffolding for the activation of the initiator caspases including caspase − 8 (extrinsic pathway), caspase − 9 (intrinsic pathway) and caspase − 3 (executioner caspase caspase-3 pathway [25,26,40,41]. The results presented in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The results of this study have revealed that M. charantia is rich in a number of cations, especially sodium and calcium, proteins, phenols, antioxidants and other compounds. Other studies have reported more than 250 bioactive compounds with medicinal and nutritious characteristics in M. charantia [41][42][43][44][45]. The question which now arises is: how MC ethanol extract and K-J exerts their lethal effect when applied extracellularly to cells in vitro.…”
Section: Discussionmentioning
confidence: 99%